O palimpsesto amoroso em Desmundo: contos de fadas - Assis, Adriana Carolina Hipolito de (2006)
This study observes the application of the palimpsest concept as a procedure capable of assisting in the novel analysis with the objective of revealing disguised narratives. When we conducted the palimpsestic scraping of the novel Desmundo, by Ana Miranda, we found a second level, another layer, where texts emerge revealing echoes of a fickle voice from oral tradition; where fairy tales, rites of passage, initiation tests and even an affection, love ideal appear, represented by the cliché of a happy end. The contribution we make using palimpsests as a novel analysis tool occurs when we associate them to reception mechanisms, which, associated with semiotic theories and based on tattooed marks found in the text, allow the reader to perceive these hermetic layers, which coexist side by side in the same narrative. Only the reader is capable of taking new bifurcated narrative paths by following the track left by the palimpsestic text